Resenha da obra de: ARAUJO, Francisco Antonio Machado; FERRO, Maria da Glória Duarte. Docência e pesquisa em formação de professores: primeiras aproximações ao objeto de estudo - OLIVEIRA, Victor Hugo Nedel (Universidade Federal do Pará, 2021)
It is a review of the work “Teaching and research in teacher training: first approaches to the object of study”, organized by professors Francisco Antonio Machado Araujo and Maria da Glória Duarte Ferro and published in 2018, by EDUFPI.